Entrepreneurship and Cities: Evidence from the Post-communist World - Maksim Belitski; Julia Korosteleva (Austrian Institute of Economic Research (WIFO), 2011)
This paper investigates the variation in entrepreneurship across cities of the Commonwealth of Independent States during 1995-2008, utilising a unique dataset and employing the System Generalised Method of Moments technique. Our findings suggest that banking reform facilitates entrepreneurship, whereas the size of the state discourages it. Our results confirm a U-shaped relationship between per-capita income and entrepreneurship. We also find that cities with higher concentration of universities are likely to have higher entrepreneurial entry. This provides some evidence for the importance of agglomeration economies in terms of higher concentration of knowledge which may lead to intensified exchange of ideas driving knowledge-based entrepreneurship in the region.
Keywords: 330; Entrepreneurship; small business; urbanisation; transition; CIS Urban Audit; Unternehmer; Unternehmensgründung; KMU; Transformationsstaaten; Momentenmethode; Schätzung; GUS-Staaten